Advances in Retinal Imaging Techniques: Oct, Fundus Autofluorescence, and Beyond - Bhoyar, Pallavi (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Retinal imaging techniques have revolutionized the field of ophthalmology by enabling non-invasive visualization of the retina, facilitating early diagnosis and management of various retinal pathologies. This paper explores recent advances in retinal imaging, focusing on Optical Coherence Tomography (OCT), Fundus Autofluorescence (FAF), and emerging modalities. OCT, a cornerstone in retinal imaging, utilizes light interference to generate high-resolution cross-sectional images of the retina, optic nerve head, and choroid. Its applications span a wide range of retinal diseases, including age-related macular degeneration, diabetic retinopathy, and glaucoma. FAF imaging, on the other hand, captures the intrinsic fluorescence emitted by retinal fluorophores, providing valuable insights into retinal pigment epithelium (RPE) health and retinal dystrophies. This paper also discusses emerging techniques such as adaptive optics imaging, multimodal imaging, and the integration of artificial intelligence (AI) in retinal imaging analysis